The Impact of Social Assistance (BPNT and PKH) Boosts Productivity in Bekasi City: Dampak Bantuan Sosial (BPNT dan PKH) mendorong Produktivfitas di Kota Bekasi - Utomo*, Kurniawan Prambudi; Fadly, Rachmat; Wardhana, Ananto Krisna; Lestiowati, Riris; Rukiastiandari, Sinta (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
The purpose of this study was to determine the effect of the BPNT and PKH variables as social assistance on Beneficiary Families (KPM) in the productivity of Bekasi City during the Implementation of Community Activity Restrictions (PPKM) Covid-19, this study used a quantitative method, with data collection methods distributing questionnaires and conducting interviews in March-April 2022 data were processed using multiple linear regression analysis with the SPSS application. The results showed that the BPNT and PKH variables had a positive and significant effect on boosting productivity in Bekasi City, in that the distribution of aid was timely and targeted according to central data, aid This helps the Beneficiary Families (KPM) in meeting temporary economic needs, until the KPM realizes that the assistance is no longer needed and is given to those who are more deserving of it in the city of Bekasi. Keywords: Impact; BPNT; PKH; Productivity; Bekasi